Pelatihan Pembuatan Soal Berbasis Digital Bagi Guru SMA di Era Revolusi Industri 4.0 - Dewi, Trie Utari; Handayani, Sri Lestari (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2020)
The challenges of the times in the era of the Industrial Revolution 4.0 or IR 4.0 need to be faced and responded by the actors in the world of education, teachers are no exception. Teachers are required to constantly innovate in learning including the evaluation process. Evaluation tools used can be technology based. The purpose of this community service activity is to conduct training on making digital-based questions using the application kahoot. This community service activity partnered with SMA PGRI 3 Jakarta. There were 22 participants in the community service activities, namely teachers at SMA PGRI 3. The method of this community service activity was distance training using the zoom meeting application. There are two sessions in this training, namely the first session in the form of understanding and strengthening related to digital literacy in the world of education and the second session in the form of a demonstration on how to make evaluation questions using the Kahoot application. After the community service, teachers and teachers at SMA PGRI 3 were able to create questions based on the Kahoot application. The final stage of this service activity was evaluated. Based on the results of the evaluation conducted by the implementation team and the school it can be stated that the training carried out was successful and went smoothly.